1991
DOI: 10.1038/ki.1991.214
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salt supplementation on amphotericin B nephrotoxicity

Abstract: It has been suggested that salt loading protects against amphotericin B-induced nephrotoxicity. The influence of saline loading on the nephrotoxic response to amphotericin B (50 mg/dose given i.v. over 4 hr 3 X/week for 10 weeks) was assessed in two groups of ten patients each who were diagnosed with mucocutaneous leishmaniasis. Patients were randomized to receive either 1 liter of 0.9% saline or 1 liter of 5% dextrose in water, administered i.v. over one hour in a double-blinded manner, directly prior to amph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0
6

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(69 citation statements)
references
References 21 publications
1
62
0
6
Order By: Relevance
“…Several studies published during the last two decades have shown that nephrotoxicity can be prevented by the use of sodium loading [4,[7][8][9][10][11], slowing drug infusion [12] and through the use of liposomal or lipid-complex amphotericins [13][14][15][16][17].…”
mentioning
confidence: 99%
“…Several studies published during the last two decades have shown that nephrotoxicity can be prevented by the use of sodium loading [4,[7][8][9][10][11], slowing drug infusion [12] and through the use of liposomal or lipid-complex amphotericins [13][14][15][16][17].…”
mentioning
confidence: 99%
“…This dose has previously been shown to cause a maximnal inhibition of 5'-nucleotidase activity 2 h after intramuscular injection (15); (iii) DB-cAMP (85 ,ug/kg/min i.a., started 30 min prior to amphotericin B and continued throughout the experiment). This dose has previously been shown to induce biological effects in the kidney, without significantly altering the baseline RBF (14); and (iv) diltiazem (20 ,g/kg/min, i.a., started 30 min prior to amphotericin B and continued throughout the experiment). This dose was found, in pilot experiments, to be the highest tolerated dose without changing baseline renal vascular resistance.…”
mentioning
confidence: 99%
“…26,76,[90][91][92][93][94][95] The risk of amphotericin-induced nephrotoxicity has been shown to double when two or more nephrotoxic agents (e.g. cyclosporin, aminoglycosides or foscarnet) are used concurrently.…”
Section: Hepatotoxicitymentioning
confidence: 99%
“…91 Sodium loading prior to amphotericin use, avoiding hypovolaemia and restricting the concomitant use of other nephrotoxins, can decrease the risk of amphotericin-induced nephrotoxicity. [94][95][96] …”
Section: Hepatotoxicitymentioning
confidence: 99%